SURVIVING TYPHOON YOLANDA (HAIYAN) IN THE LENS OF COMTEAN ALTRUISM - Bautista, Dennis Moreto (International Journal of Humanity Studies (IJHS), 2020)
Altruism for August Comte is a belief of disinterestedness and an unselfish concern for other people. It is a theory that postulates the generous side of a person even in times of difficulty and even death. The onslaught of the strongest typhoon ever recorded in history brought substantial damage to different spheres of a human life. Despair and unwillingness to live were evident. However, despite severe damage to both body and soul to almost everyone in the hardest-hit areas, the victims managed to survive, share, and assist even the minutest that they have to others. Supplies were depleted and people have nowhere to buy food and other necessary elements. This study collected narrative experiences from individuals who were caught up in the storm and its aftermath. The study utilized the philosophical and critical social type of qualitative research, which aims to provide knowledge, which involve the existing social structure.Â  This described, evaluated, and interpreted the different personal experiences of Yolanda survivors anchored on the Comtean philosophy of altruism.